Growth and Yield of Different Castor Genotypes Varying in DroJght Tolerance - Lakshmamma, P; Prayaga, Lakshmi; Lavanya, C; Anjani, K (Annals of Arid Zone, 2016)
An experiment was conducted to evaluate twelve castor germplasm line stOlerant to fusarium wilt and differing in bloom/ epicuticular wax load) under drought d ring rabi 2005-06 in split plot design with three replications. Stress was imposed by wi olding irrigation from 45-120 DAS (stress-I) or 65-120DAS (stress-2). Total dry matter (’IbM) and seed yield significantly reduced with stress. Control plants recorded 62.2 g see4 planrt, whereas stressed plants recorded 42.2, 42.4 g planri in stress-l and stress-2, re’s eCtivelY’ Lines RG 2317,RG 923 recorded <30%yield reduction and <0.5 drought susceptibil’ty index (DSI)in both stress treatments. There was significant increase in epicuticular wax 10 /bloom due to stress i.e. 18.6%in SI and 17.1%in S2 compared to control. Genotypes als showed similar response except DPC-9, DPC-lO, which are of zero bloom type pistillate lines and DCS-86,a breeding line. RG 2317,which is a mild triple bloom type, recorded higher bloom content both in control and under stress compared to other genotypes. l Key words: Castor, EWL/bloom, stress, drought susceptibility index (DSI Â